2014
DOI: 10.1016/j.bbmt.2014.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Immune Cell Subset Counts Associated with Graft-versus-Host Disease

Abstract: Graft-versus-host disease (GVHD) is a major transplantation complication. The purpose of this study was to measure immune cell subsets by flow cytometry early after transplantation (before median day of GVHD onset) to identify subsets that may play a role in GVHD pathogenesis. We also measured the subsets later after transplantation to determine which subsets may be influenced by GVHD or its treatment. We studied 219 patients. We found that acute GVHD (aGVHD) was preceded by high counts of CD4 T cells and CD8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 67 publications
(71 reference statements)
5
53
0
Order By: Relevance
“…Chronic GvHD was, as expected, the second major event to shape long-term immune reconstitution. Chronic GvHD has already been reported to influence Band T-cell reconstitution 3,8,9,20,21,43,44 but none of these studies provided a broad overview as allowed here by CA. It is interesting to note that CMV-specific memory T cells cross react with alloantigens 45,46 and have long been suspected to be involved in the pathogenesis of GvHD through molecular mimicry.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Chronic GvHD was, as expected, the second major event to shape long-term immune reconstitution. Chronic GvHD has already been reported to influence Band T-cell reconstitution 3,8,9,20,21,43,44 but none of these studies provided a broad overview as allowed here by CA. It is interesting to note that CMV-specific memory T cells cross react with alloantigens 45,46 and have long been suspected to be involved in the pathogenesis of GvHD through molecular mimicry.…”
Section: Discussionmentioning
confidence: 97%
“…2,3 Several studies have pinpointed the role of transplant characteristics, including conditioning regimen intensity, source of stem cells and donor matching, [4][5][6][7] and that of post-transplant events including acute (aGvHD) and chronic (cGvHD) graftversus-host disease and infections such as cytomegalovirus (CMV) replication on post-transplant immune reconstitution. [8][9][10] Other studies have focused on the study of a distinct subset of immune cells, e.g. regulatory T cells (Tregs), CD5 + B cells, or NK cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that phenotypic and functional recovery of donor T cells is often delayed for months to years after allogeneic HSCT. [1][2][3][4] Although most studies have focused on reconstitution of effector T cells, several studies have also examined recovery of CD4 regulatory T cells (CD4Tregs). [5][6][7][8][9] These studies suggest that CD4Treg deficiency can enhance alloreactivity and promote graftversus-host disease (GVHD).…”
Section: Introductionmentioning
confidence: 99%
“…After allogeneic HSCT in humans, it is possible that aGVHD responses evolve as naïve T cells are activated by alloantigens and then proliferate and differentiate into memory subsets with effector functions. The recent observation in humans of increased numbers of CD4 þ and CD8 þ TEM cells at day þ28 after HSCT in patients who developed aGVHD suggests that TEMs play a role in aGVHD [27]. Interestingly, 2 early flow cytometric human studies that examined total CD4 þ and CD8 þ T cell populations in patients after allogeneic HSCT noted a predominant association of aGVHD with peripheral blood CD8 þ T cell populations or with decreasing CD4 to CD8 ratios, suggesting that CD8 þ T cell expansion plays an important role in human aGVHD [28,29].…”
Section: Introductionmentioning
confidence: 99%